Use of a gray level co-occurrence matrix to characterize duplex stainless steel phases microstructure - L. Zortea; F. R. Renzetti (Fracture and Structural Integrity)
Duplex stainless steels are widely used in industry. This is due to their higher strength compared to austenitic steels and to their higher toughness than ferritic steels. They also have good weldability and high resistance to stress corrosion cracking.These steels are characterized by two-phase microstructures composed by almost the same level of ferrite and austenite.Duplex steel 2205 samples evaluated are: as received, cold rolled (33%) and heat-treated at 800°C for 10 hours.A metallographic etching with 10% oxalic acid has been carried out to highlight the phases morphology. Some photos have been taken by SEM microscope and submitted to image analysis. The analysis carried out is based on the determination of co-occurrence matrix and on the following interpretation of appropriate indicators. Through these indicators is possible to estimate the features of images objectively.